2018
DOI: 10.1097/md.0000000000013606
|View full text |Cite
|
Sign up to set email alerts
|

Persistent HPV-16 infection leads to recurrence of high-grade cervical intraepithelial neoplasia

Abstract: High-grade cervical intraepithelial neoplasia (CIN) is a precancerous lesion of cervical cancer. The aims of this study were to evaluate the risk factors for recurrence of high-grade CIN and to determine if the specific genotype of human papillomavirus (HPV) is a predictor of recurrent high-grade CIN. Between January 2010 and December 2014, 172 patients with CIN 2+ underwent cold knife conization or a loop electrosurgical excision. The HPV DNA chip was used to detect HPV. Recurrent lesions were histologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…HPV infection is relatively common among females (28,29). Persistent HPV infection may cause intraepithelial pre-neoplastic lesions and invasive cervical cancer (30,31). The present study revealed that the positivity rates of HPV and HPV16 in patients with cervical cancer were 77.03 and 52.07%, respectively, which were significantly higher compared with the controls.…”
Section: Discussionmentioning
confidence: 44%
“…HPV infection is relatively common among females (28,29). Persistent HPV infection may cause intraepithelial pre-neoplastic lesions and invasive cervical cancer (30,31). The present study revealed that the positivity rates of HPV and HPV16 in patients with cervical cancer were 77.03 and 52.07%, respectively, which were significantly higher compared with the controls.…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, the possibility of re-infection after treatment should be considered. Infact, Jung Mi Byun et al [13] during follow-up, 70.7% of HPV infections were new and 29.3% were persistent, indicating a need to prevent reinfection after treatment and to regular follow-up for persistent HPV infection. HPV vaccination for HPV 16 type may be useful in preventing recurrence of CIN 2/3 and CIS.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a recent study, rate of persistence of high grade CIN after treatment was 25.7% and it has been shown to be mostly associated with persistent HPV 16 infection. 19 In our study, 50% of patients with different range of HPV viral load, were having persistent CIN lesions, with 31% having CIN2-3. Prognosis was strictly independent to the HPV viral load, and chance of recurrence of cervical lesions (CIN1, CIN2-3) or having better prognosis after treatment was almost the same in all patients whatever how high or low their HPV-HC2 viral load was.…”
Section: Discussionmentioning
confidence: 45%